Standalone cohesin as a molecular shuttle in cellulosome assembly. Issue 14 (17th April 2015) - Voronov-Goldman, Milana; Yaniv, Oren; Gul, Ozgur; Yoffe, Hagar; Salama-Alber, Orly; Slutzki, Michal; Levy-Assaraf, Maly; Jindou, Sadanari; Shimon, Linda J.W.; Borovok, Ilya; Bayer, Edward A.; Lamed, Raphael; et al.
Abstract : The cellulolytic bacterium Ruminococcus flavefaciens of the herbivore rumen produces an elaborate cellulosome system, anchored to the bacterial cell wall via the covalently bound scaffoldin ScaE. Dockerin‐bearing scaffoldins also bind to an autonomous cohesin of unknown function, called cohesin G (CohG). Here, we demonstrate that CohG binds to the scaffoldin‐borne dockerin in opposite orientation on a distinct site, relative to that of ScaE. Based on these structural data, we propose that the complexed dockerin is still available to bind ScaE on the cell surface. CohG may thus serve as a molecular shuttle for delivery of scaffoldins to the bacterial cell surface.